NILAI MORAL TOKOH-TOKOH UTAMA DALAM KUMPULAN CERITA RAKYAT LEGENDA SI PAHIT LIDAH KARYA MB. RAHIMSYAH - Diyani Purnama Sari; Sainil Amral; Harbeng Masni (Universitas Batanghari, 2020)
The purpose of this research is to describe good and bad moral values related to the relationship between humans and the relationship between humans and the environment in the collection of folklore Cerita Rakyat Legenda Si Pahit Lidah by MB. Rahimsyah. This research is qualitative descriptive which describes expressions contained in the collection of folklore Cerita Rakyat Legenda Si Pahit Lidah by MB. Rahimsyah. The data used in this research is primary data in the form of expressions containing moral values in the collection of folklore Cerita Rakyat Legenda Si Pahit Lidah by MB. Meanwhile the secondary data is in the form of books related to the research. The results of the research showed that there are 102 expressions in the collection of the Folklore Cerita Rakyat Legenda Si Pahit Lidah by MB. Rahimsyah. There are 4 forms of good moral value of the relationship between humans to humans, they are: 1) 5 expressions of fair, 2) 23 expressions of being helpful, 3) 3 expressions of forgiveness, and 4) 12 expressions of keeping promises. Moreover, there are also 4 forms of bad moral value of the relationship between humans to humans, they are: 1) 11 expressions of cheating, 2) 25 expressions of ignoring others, 3) 4 expressions of vengeful, and 4) 6 expressions of breaking promises. There is one form of good moral value in the relationship between humans and the environment. It is called maintaining the environment in which there are 3 expressions found in the data. Meanwhile bad moral value of the relationship between humans and the environment are also found in the data. There are 10 expressions of it and it is called damaging the environment.